2017
DOI: 10.1038/s41598-017-06475-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiview three-dimensional reconstruction by millimetre-wave portable camera

Abstract: Millimetre-wave imaging is a powerful non-destructive inspection technique which has become widely used in areas such as through-the-wall imaging or concealed weapon detection. Nevertheless, current systems are usually limited to either a single view point providing a limited 3D millimeter-wave model or a multiview relying on the accurate movement of a robot arm through precise positions resulting in very bulky systems. In this paper, we present a set of techniques to achieve a multiview millimetre-wave scanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Future use‐cases for this technology could include using the breathing and cardiac signals to model motion for 4D‐CT or respiratory‐gated treatments. The mmWave technology also has the potential to be used as an alternative method for surface reconstruction, which can be achieved by synthetic aperture radar (SAR) or inverse synthetic aperture radar (iSAR) . Compared with optical surface reconstruction, mmWave surface reconstruction is not sensitive to skin color and may penetrate the face mask or other fixture devices.…”
Section: Discussionmentioning
confidence: 99%
“…Future use‐cases for this technology could include using the breathing and cardiac signals to model motion for 4D‐CT or respiratory‐gated treatments. The mmWave technology also has the potential to be used as an alternative method for surface reconstruction, which can be achieved by synthetic aperture radar (SAR) or inverse synthetic aperture radar (iSAR) . Compared with optical surface reconstruction, mmWave surface reconstruction is not sensitive to skin color and may penetrate the face mask or other fixture devices.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion to conventional optical cameras, in this work microwave data is acquired from different positions resulting from arbitrary movements. The feasibility of this novel concept was initially demonstrated in [18] by merging optical cameras and SAR imaging resulting from moving/scanning a single transceiver to synthesize the aperture. Furthermore, it was demonstrated that the proposed algorithms could also yield 3D object surface profile, obtained from the optical camera, and images of the interior of the object, obtained from the electromagnetic imaging data.…”
Section: Introductionmentioning
confidence: 99%
“…Further research to extend [18] was focused on sparse data collection to reduce the number of antenna elements for the multi-view imager [19] as well as on replacing the conventional optical camera by one capable of producing object depth information [20], which can provide not only the RGB values of each pixel but also its depth. This is important since this also improves pixel position accuracy for texture-less objects (e.g., plain clothing).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these techniques from CV have been recently adapted to SAR approaches to bypass the aforementioned problems [6]. Furthermore, these techniques are mainly developed for relatively small scanners, which can be arbitrarily moved, in contrast to bulky scanners, but they are only able to image a smaller volume as a consequence of their smaller size.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these techniques are mainly developed for relatively small scanners, which can be arbitrarily moved, in contrast to bulky scanners, but they are only able to image a smaller volume as a consequence of their smaller size. In this contribution, these techniques are applied for the first time to a recently-developed real-time microwave camera [7] in place of the usual raster scanning [6]. This step provides an intermediate milestone towards the possibility of developing a portable free-hand scanner.…”
Section: Introductionmentioning
confidence: 99%